Poor sleep quality is associated with fatigue and depression in early Parkinson's disease: A longitudinal study in the PALS cohort - Koh, Matthew Rui En; Chua, Cong Yang; Ng, Samuel Yong-Ern; Chia, Nicole Shuang-Yu; Saffari, Seyed Ehsan; Chen, Regina Yu-Ying; Choi, Xinyi; Heng, Dede Liana; Neo, Shermyn Xiumin; Tay, Kay Yaw; Au, Wing Lok; Tan, Eng-King; et al. (Frontiers in Neurology, 2022)
Background: Sleep disorders are common in Parkinson’s Disease (PD). However, the longitudinal relationship between sleep quality and the other non-motor symptoms of PD has not been well characterised, especially in early PD. Objective: To explore the value of baseline sleep quality in predicting the progression of other non-motor symptoms in early PD. Methods: 109 early PD patients were recruited to the study. Patients were stratified into good and poor sleepers using the Pittsburgh Sleep Quality Index (PSQI). Assessments performed at baseline and one year follow-up included the Epworth Sleepiness Scale, Fatigue Severity Scale, Non-Motor Symptom Scale, Geriatric Depression Scale, Hospital Anxiety and Depression Scale, Apathy Scale, Montreal Cognitive Assessment and detailed neuropsychological assessments. Multivariable linear regression was performed at baseline to investigate differences in clinical scores between poor and good sleepers, while multivariable regression models were used to investigate associations between sleep quality and progression of test scores at one year follow-up. Results: 59 poor sleepers and 50 good sleepers were identified. At baseline, poor sleepers had greater HADS anxiety scores (p=0.013) [2.99 (95%CI 2.26, 3.73)] than good sleepers [1.59 (95%CI 0.75, 2.42)]. After one year, poor sleepers had greater fatigue (FSS scores +3.60 as compared to -2.93 in good sleepers, p=0.007) and depression (GDS scores +0.42 as compared to -0.70, p=0.006). Conclusion: This study shows a longitudinal association between sleep quality, fatigue, and depression in early PD patients, independent of medication effect and disease severity, This may support the hypothesis that a common serotonergic pathway is implicated in these non-motor symptoms.